2017
DOI: 10.3389/fmicb.2017.00105
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Generation and Its Involvement in the Growth of Mycobacterium smegmatis

Abstract: Superoxide generation is inevitable in aerobic organisms, most of which have developed mechanisms to detoxify superoxides. However, its significance has not been clearly understood in mycobacteria. This study demonstrates that NADH oxidase is the major source of superoxide in Mycobacterium smegmatis and elucidates the involvement of superoxide in M. smegmatis growth. The maximum inhibition of superoxide generation was observed in the presence of diphenyleneiodonium chloride (DPI), an NADH oxidase inhibitor, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…To determine comparative levels of superoxide production under different dormancy conditions, the dihydroethidium (DHE)-HPLC method was used [16]. Briefly, DHE (50 μM) was added to 17.5 mL of the following cultures: untreated aerobically growing culture (~0.35 OD 600 nm ), DPI treated culture (4 μg/mL, 24 h), Vitamin C treated culture (10 mM, 24 h) and Wayne hypoxic dormant culture (16 days) in 20 mm × 125 mm tubes and incubated for 90 minutes in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine comparative levels of superoxide production under different dormancy conditions, the dihydroethidium (DHE)-HPLC method was used [16]. Briefly, DHE (50 μM) was added to 17.5 mL of the following cultures: untreated aerobically growing culture (~0.35 OD 600 nm ), DPI treated culture (4 μg/mL, 24 h), Vitamin C treated culture (10 mM, 24 h) and Wayne hypoxic dormant culture (16 days) in 20 mm × 125 mm tubes and incubated for 90 minutes in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Ascorbic acid (10 mM), an antioxidant also reported to induce dormancy and VBNC phenotypes in Mtb [1415], indicates the role of reactive oxygen species (ROS) scavenging during the development of a dormant form. Superoxide, a reactive oxygen species generated during electron transfer reactions in NADH oxidase, can be inhibited by diphenyleneiodonium (DPI) [16]. Yeware et al (2017) have described how DPI inhibits superoxide production as well as growth of M .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While traditionally considered a threat to cellular viability, there are cases where microbes exploit ROS for their own benefit. Intracellular superoxide can serve as a signal for development in eukaryotes (Bloomfield and Pears, ; Finkel, ; Mittra and Andrews, ), and as a growth factor for the bacterium Mycobacterium smegmatis (Yeware et al ., ) and the eukaryotic red tide phytoplankter Chattonella marina (Oda et al ., ). As we will see later, marine microbes may generate extracellular normalO2 to enhance the uptake of iron.…”
Section: Introductionmentioning
confidence: 99%
“…Yeware et al (2017), observed no effect of PEG-SOD on either growth or superoxide production in cells, which they interpret as non-permeability of PEG-SOD. Moreover, in crude membrane preparation PEG-SOD could barely inhibit 0.37 folds of 2-OH-E + .…”
mentioning
confidence: 98%